Psychosocial, education, economic factors, decision-making ability, and caries status of mothers of children younger than 6 years in suburban Nigeria - Morenike Oluwatoyin Folayan; Maha El Tantawi; Ayodeji Oginni; Abiola Adeniyi; Michael Alade; Tracy L. Finlayson (BMC, 2020)
Abstract Background Little information is available on the relationship between mothers' psychosocial profile and caries status, and less information is available on the oral health status and psychosocial status of mothers of young children in Africa. This study examined the association between the psychosocial profile of mothers in Nigeria and their prevalence of caries. Methods The prevalence of caries and severe caries (DMFT > 3) in mothers with children 71 months old and younger recruited through a household survey in Ile-Ife, Nigeria, was estimated through clinical examination. The explanatory variables were maternal education, income, decision-making status, and psychosocial status (dental anxiety, general anxiety, depressive symptoms, parenting stress, executive dysfunction, sense of coherence, fatalism and social support). The risk indicators for maternal caries were analyzed with logistic regression. Results The prevalence of caries was 3.3%. Twenty (39.2%) of the 51 women with caries had DMFT > 3. Most study participants were 25-34 years old (59.3%), had secondary level education (63.1%), earned N18,000 ($49)-N30000 ($84) per month (42.9%), and can make autonomous decisions about their health care, household purchases, or visits to family/relatives (68.8%). Most women had normal general anxiety (79.9%), low dental anxiety (90.4%), and normal stress (76.4%) levels. Most also had high fatalism (56.6%), perceived moderate social support (81.6%), had normal depressive symptoms (75.9%), low executive dysfunction (55.9%), and high sense of coherence (53.8%). Mothers who had clinically significant levels of stress were twice more likely to have caries than were those whose level of stress was normal (AOR: 2.26; 95%CI: 1.04-4.89; P = 0.039). Also, mothers who had high fatalism were less likely to have caries than were those with low fatalism (AOR: 0.40; 95%CI: 0.21-0.75; P = 0.004). Conclusion High levels of parenting stress was a risk indicator for caries while high fatalism was protective from caries in mothers of children younger than 6-years. Maternal education, income and decision-making ability were not associated with maternal caries. Though the caries prevalence for women with young children was low, the prevalence of severe caries was high and this because of the possible negative effect on their health and wellbeing.